2013
DOI: 10.1080/14330237.2013.10820619
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Mediating Effect of Open Distance Learning Students' Study Engagement in Relation to Their Life Orientation and Self-Efficacy

Abstract: This study reports on the mediating effect of study engagement (measured by an adapted version of the Utrecht Work Engagement Scale) in relation to students' life orientation (measured by the Orientation to Life Questionnaire) and their self-efficacy (measured by the Self-efficacy Scale). Participants included a non-probability sample of 127 predominantly early career (25-40 years), employed blacks and females enrolled for third year level ODL undergraduate studies in Industrial and Organisational Psychology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The positive relation between the participants' factual practical learning strategies and their self-efficacy, career resilience and proactivity may be attributed to the proposition made by Dooley, Linden and Dooley (2005) that learning seems to improve when learners have the opportunity to practise and experiment with what and how they learn. Experiential learning increases learners' levels of active study engagement (Robinson, 2006), which, in turn, has been shown to enhance their confidence in their abilities to successfully perform and persevere in complicated situations (Coetzee & Oosthuizen, 2013). Using practical factual information to solve problems and make decisions that apply to real-world situations also increases adult learners' sense of self-directedness and intrinsic learning motivation (Coetzee & Botha 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive relation between the participants' factual practical learning strategies and their self-efficacy, career resilience and proactivity may be attributed to the proposition made by Dooley, Linden and Dooley (2005) that learning seems to improve when learners have the opportunity to practise and experiment with what and how they learn. Experiential learning increases learners' levels of active study engagement (Robinson, 2006), which, in turn, has been shown to enhance their confidence in their abilities to successfully perform and persevere in complicated situations (Coetzee & Oosthuizen, 2013). Using practical factual information to solve problems and make decisions that apply to real-world situations also increases adult learners' sense of self-directedness and intrinsic learning motivation (Coetzee & Botha 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy beliefs help determine how much effort people will expend on an activity, how long they will persevere when confronting obstacles and how resilient they will prove to be in the face of adverse and stressful situations: the higher the sense of self-efficacy, the greater the effort, persistence and resilience (Coetzee & Oosthuizen, 2013;Pajares, 1996). The positive relation between the participants' factual practical learning strategies and their self-efficacy, career resilience and proactivity may be attributed to the proposition made by Dooley, Linden and Dooley (2005) that learning seems to improve when learners have the opportunity to practise and experiment with what and how they learn.…”
Section: Discussionmentioning
confidence: 99%